Do we know about dynapenia? - Sivritepe, Rıdvan; Kıran Siyer, Özge; Tiril, Serhat Mert; Uçak Basat, Sema (My University, 2024)
Dynapenia is a condition characterized by decreased muscle strength and function in older adults that is not due to a spe-cific underlying disease or medical condition. Dynapenia is common among older adults and has significant health effects, including functional impairment, disability, increased risk of falls, hospitalization, and death. Oxidative stress, mitochondrial dysfunction and chronic inflammation are involved in the etiopathophysiology of dynapenia. Diagnosis of dynapenia is based on the evaluation of muscle strength and function using methods such as hand grip strength, timed up and go test and short physical performance battery. Management of dynapenia involves a multifaceted approach that includes exercise, nutrition, pharmacological interventions, management of underlying medical conditions, and fall prevention strategies. With appropriate interventions, older adults with dynapenia can improve muscle strength and function, reduce the risk of falls and disability, and maintain their independence and quality of life.
Dinapeniyi biliyor muyuz?
Keywords: Dynapenia; Geriatrics; Muscle Strength